A defoaming agent for cementing and preparation method thereof
By using emulsifiers, polyether modified silicone oil and modified nanosilicon dioxide in cementing cement, the shortcomings of existing defoamers in anti-seepage and shrinkage resistance are solved, and better defoaming effect and cement slurry performance are achieved.
Patent Information
- Application Number
- CN202411285804.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The defoaming agents used in cementing cement in the prior art perform poorly in terms of anti-seepage and shrinkage properties, limiting their application range.
A defoaming agent for cementing cementing cement is adopted, which includes emulsifier, polyether modified silicone oil, thickener, dispersant, modified nanosilica and water. Through the synergistic action of polyether modified silicone oil and modified silicon dioxide, the defoaming effect is improved and the rheological performance, shrinkage resistance and permeability of the cement slurry are improved.
The defoamability and foam suppression ability of the defoaming agent are significantly improved, the quality and mechanical properties of the cement slurry are enhanced, the effect and efficiency of cementing operations are optimized, and the anti-seepage and shrinkage properties of the cement are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement additives, and in particular to a defoamer for cementing cement and a preparation method thereof. Background Art
[0002] As a commonly used cementing material, cement-based materials are widely used in downhole reinforcement projects for oil and gas well drilling and completion operations. Cement materials have the advantages of high strength and simple production, but due to their own brittleness and low tensile strength, they have many durability problems. With the increase in the exploration of oil and gas wells, high mineralization and increasing bottom hole temperature and pressure will be encountered during cementing operations, which can easily cause problems such as unstable cement slurry system, cement corrosion and poor mechanical properties. In order to ensure the cementing quality of cementing cement, organic polymers can be added to cementing cement to improve the durability, mechanical properties and corrosion resistance of cementing cement.
[0003] A large amount of foam in industrialization will affect the production process control and product quality. To reduce or eliminate foam, the most direct way is to use a defoamer. In the preparation process of cement mortar, defoamers are often widely used as substances to control and reduce the number of bubbles in mortar. The addition of defoamers can eliminate large bubbles in mortar, which helps to improve the strength of mortar. The effect on bubbles will inevitably cause changes in the pore structure of mortar, which will in turn affect the drying shrinkage of mortar. Therefore, it is necessary to discuss the influence of defoamers on the drying shrinkage of polymer-modified cement mortar, and whether the co-addition of defoamers and shrinkage reducers will have a synergistic effect on the drying shrinkage of polymer-modified cement mortar, so as to expand the application scope of shrinkage reducers in cement-based materials.
[0004] A large number of studies have shown that the introduction of nanomaterials can improve the density, compression resistance, tensile strength and toughness of cement paste. Further research has also found that the introduction of a certain amount of nano-silicon dioxide can also significantly increase the thermal stability of the cement slurry system and effectively slow down the decline of the strength of cement paste. The introduction of nano-silicon dioxide has higher compressive strength than cement paste mixed with silica fume under high temperature conditions. Nano-silicon dioxide usually has a particle size of only tens of nanometers, which can well fill the pores of cement paste, thereby reducing the spatial pore structure of cement paste and enhancing the density. Silicone defoamers have low surface tension, stable chemical properties, high safety performance, and are incompatible with various substances, and have good defoaming and anti-foaming properties; the biggest advantage of polyether defoamers is their strong anti-foaming ability, high temperature resistance, strong acid and alkali resistance, etc. Polyether-modified silicone defoamers are polysiloxane chains and polyethers connected together, so that they have the advantages of both silicone defoamers and polyether defoamers.
[0005] Chinese invention patent CN115594838B discloses a defoaming branched condensate, a defoamer composition and a preparation method thereof. The defoaming composition comprises a carrier, a branched condensate, an emulsifier, water, a preservative and a stabilizer, wherein the water, the emulsifier and the stabilizer can make the branched condensate be a stable dispersion of fine particles, can be fully mixed with the carrier but avoid direct contact, significantly reduce the oxygen content in concrete and improve the strength of concrete, increase the speed of bubble merging, and help to suppress foaming and defoaming. Although the invention has achieved beneficial technical effects, the invention still has a problem that the impermeability and shrinkage resistance added to the cement mortar are not good, which still limits its application. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a defoaming agent for cementing and a preparation method thereof.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] A defoamer for cementing wells comprises the following raw materials in percentage by mass: an emulsifier, a defoaming aid, a thickener, a dispersant, an inorganic filler and water.
[0009] Preferably, the defoamer for cementing cement comprises the following raw materials in percentage by weight: 5-10wt% emulsifier, 4-7wt% defoaming aid, 1-3wt% thickener, 2-6wt% dispersant, 8-20wt% inorganic filler, and the balance is water.
[0010] The emulsifier is any one of castor oil polyoxyethylene ether, polyethylene glycol dilaurate, sorbitan polyoxyethylene ether fatty acid ester and Tween 80.
[0011] The defoaming aid is any one of polyether modified silicone oil and amide surfactant.
[0012] The role of polyether modified silicone oil as a defoaming agent in cementing cement is to help reduce the formation of bubbles in cement slurry, thereby improving the fluidity and stability of cement slurry and ensuring the smooth progress of cementing operations. In cementing operations, cement slurry is injected into the wellbore to block the space around the wellbore, protect the well wall, strengthen the wellbore structure, and prevent groundwater and oil and gas from penetrating from the wellbore. However, cement slurry is prone to bubbles during the injection and solidification process, which can cause the rheological properties of cement slurry to deteriorate and even affect the sealing effect and strength of cementing.
[0013] Preferably, the defoaming aid is a polyether-modified silicone oil, and the preparation method of the polyether-modified silicone oil is as follows: under nitrogen protection, benzyl silicone oil, (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide, decanol and chloroplatinic acid are added and mixed, heated to react, and then allyl polyoxyethylene methyl-terminated polyether is added to continue the reaction, and the solvent is evaporated under reduced pressure to obtain polyether-modified silicone oil.
[0014] The present invention adds polyether-modified silicone oil as a defoaming aid to the defoamer for cement, which can solve the problems of weak defoaming property and low foam suppression ability of the defoamer. As a defoaming aid, the polyether-modified silicone oil can effectively reduce the formation of bubbles in cement slurry. It hinders the formation and aggregation of bubbles by reducing the surface tension of the cement slurry, thereby reducing the number and size of bubbles in the cement slurry. This allows the cement slurry to fill the wellbore more evenly, reduces voids and defects, improves the cementing effect and the sealing performance of the cement slurry, and improves the anti-seepage performance of the cement; the polyether-modified silicone oil can be dispersed into fine particles through the emulsifying function of the emulsifier, which is conducive to the spreading of the polyether on the foam surface, better inhibiting the formation of foam or breaking the foam, thereby improving the defoaming property of the defoamer.
[0015] Furthermore, the preparation method of the polyether-modified silicone oil is as follows: under nitrogen protection, 2-5 parts by weight of benzyl silicone oil, 2-5 parts by weight of (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide and 0.2-0.7 parts by weight of n-decanol and chloroplatinic acid are added and mixed, wherein the amount of chloroplatinic acid added is 0.005-0.02wt% of the mass of the benzyl silicone oil, the mixture is reacted at 80-100°C and 300-600rpm for 1-4h, 2-5 parts by weight of allyl polyoxyethylene methyl-terminated polyether is added and the reaction is continued for 3-8h, and the solvent is evaporated under reduced pressure to obtain a polyether-modified silicone oil.
[0016] The thickener is any one of xanthan gum, sodium alginate, sodium starch phosphate and sodium alginate.
[0017] The dispersant is any one of polyethylene glycol, polyvinyl alcohol, polyethyleneimine and tributyl phosphate.
[0018] The inorganic filler is nano silicon dioxide or modified nano silicon dioxide.
[0019] The size of nano-scale silica particles increases the specific surface area. The number of atoms on the surface of the modified nano-silica is large, and the surface energy and surface tension increase sharply with the decrease of particle size. There are a large number of active hydroxyl groups on the surface of nano-silica, which are chemically reactive and have strong hydrophilic properties. However, due to the small particle size of nanomaterials, they are easy to agglomerate in the polymer system, resulting in uneven dispersion of nanomaterials.
[0020] The modified silica used in the present invention can effectively hinder the formation and aggregation of bubbles. Its special surface properties and structure can form a microstructure similar to a mesh structure in the cement slurry, hindering the diffusion and aggregation of bubbles in the cement slurry, thereby effectively reducing the number and size of bubbles and improving the defoaming effect. As an inorganic filler, modified silica has excellent mechanical properties and stability, can effectively increase the cohesion and impermeability of cement slurry, and has good dispersibility and surface activity. It can effectively interact with cement particles to form a uniform and stable cement slurry structure. This structure helps to improve the fluidity and pumpability of cement slurry, making it easier to flow and fill in the wellbore, thereby improving the rheological properties of cement slurry and improving the shrinkage resistance and impermeability of cement.
[0021] In summary, adding modified silica as an inorganic filler for defoaming agent can play an important role in cementing cement. It can not only enhance the defoaming effect, but also improve the rheological properties, anti-shrinkage properties and anti-permeability properties of cement slurry, reduce cementing costs, and provide better technical support and economic benefits for cementing operations.
[0022] The preparation method of the modified nano-silica comprises the following steps: N1 taking nano-silica and dispersing it in water, adding N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane for reaction, and obtaining silane-modified nano-silica;
[0023] N2 Under nitrogen protection, the above silane-modified nano-silica was dispersed in water, stirred at room temperature, N-vinyl-N-methylacetamide and ammonium persulfate were added, and heated to react to obtain modified silica.
[0024] Preferably, the preparation method of the modified nano-silicon dioxide comprises the following steps:
[0025] N1: 6-8 parts by weight of nano-silica are dispersed in 25-60 parts by weight of water, 1-3 parts by weight of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane are added, the pH is adjusted to 4-5, and the mixture is reacted at 70-90° C. and 300-500 rpm for 1-4 hours, then cooled to room temperature, centrifuged, washed, and freeze-dried to obtain silane-modified nano-silica;
[0026] N2 Under nitrogen protection, take 3-7 parts by weight of the above-mentioned silane-modified nano-silica and disperse it in 50-100 parts by weight of water, stir it at room temperature and 500-800 rpm for 8-15 minutes, add 3-5 parts by weight of N-vinyl-N-methylacetamide and 0.03-0.1 parts by weight of ammonium persulfate, continue stirring for 5-12 minutes, react at 400-800 rpm and 70-90°C for 4-10 hours, wash and dry to obtain modified silica.
[0027] The present invention uses polyether-modified silicone oil and inorganic filler as main defoaming components, effectively reduces surface tension and improves defoaming efficiency; polyether-modified silicone oil effectively improves the dispersibility of defoaming active substances in cement mortar due to the introduction of hydrophilic polyether segments, and is easy to play a defoaming and decompression role in the cement mortar system. Adding polyether-modified silicone oil and modified silicon dioxide as defoamers to cement at the same time has an obvious synergistic effect, making the two more compatible, and also enhancing the defoaming performance of the two, while improving the anti-shrinkage performance and anti-permeability performance of cement. The specific synergistic effects are as follows: (1) Polyether-modified silicone oil and polysilane-modified silica have different defoaming mechanisms and modes of action, respectively. Using them together can comprehensively utilize the advantages of the two defoaming agents, effectively reduce the formation and aggregation of bubbles in cement slurry, and thus further improve the quality and mechanical properties of cement slurry; (2) Adding them to cement at the same time can not only eliminate bubbles, but also improve the rheological properties and stability of cement slurry. The synergistic effect of the two can make the cement slurry more uniform and dense, reduce the difference in fluidity, and improve the stability and sealing of cementing; (3) It can make cement slurry easier to pump and fill, reducing the time and cost of cementing operations. By improving the fluidity and pumpability of cement slurry, the synergistic effect helps to improve construction efficiency and reduce resource waste; (4) It can also optimize the flow characteristics and bonding properties of cement slurry, so that it can better contact with the well wall and fill the wellbore, improving the cementing effect and the safety and stability of the wellbore.
[0028] Therefore, by using polyether-modified silicone oil and polysilane-modified silica as defoamers in cement at the same time, the defoaming effect can be synergistically enhanced, the quality and mechanical properties of the cement slurry as well as the anti-permeability performance can be improved, and the effect and efficiency of the cementing operation can be optimized.
[0029] The preparation method of the defoamer for cementing cement comprises the following steps:
[0030] S1 weigh the above raw materials according to weight;
[0031] S2: adding emulsifier, defoaming agent, thickener, dispersant, inorganic filler and water into a reaction kettle, heating and stirring at 45-60° C. and 600-1500 rpm for 20-40 minutes to obtain a defoaming agent for cementing cement.
[0032] Beneficial effects of the present invention: The present invention provides a defoamer for cementing and a preparation method thereof. The present invention adds modified nano-silicon dioxide and polyether-modified silicone oil to the preparation method of the defoamer for cementing. By using polyether-modified silicone oil and modified silicon dioxide as defoamers in cement at the same time, nano-silicon dioxide usually has a particle size of only tens of nanometers, which can better fill the pores of cement stone, thereby reducing the spatial pore structure of cement stone and enhancing density, and having higher compressive strength; polyether-modified silicone oil has good defoaming and anti-foaming properties; the simultaneous use of the two can not only achieve synergistic enhancement of the defoaming effect, but also improve the quality, anti-shrinkage and anti-permeability properties of cement slurry, and optimize the effect and efficiency of cementing operations. DETAILED DESCRIPTION
[0033] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0034] Introduction of some raw materials in this application:
[0035] Castor oil polyoxyethylene ether was purchased from Xingtai Xinlanxing Technology Co., Ltd., model: C-125.
[0036] Allyl polyoxyethylene methyl terminated polyether was purchased from Hubei Langbowan Biopharmaceutical Co., Ltd., item number: LBW-0171.
[0037] Polyvinyl alcohol was purchased from Wuhan Runxingyuan Technology Co., Ltd., model: PVA1788.
[0038] Nano-silica was purchased from Beijing Dekedaojin Technology Co., Ltd., model: DK-silica-15.
[0039] Example 1
[0040] A defoamer for cementing cement comprises the following raw materials in percentage by mass: 8wt% of castor oil polyoxyethylene ether, 5wt% of defoaming aid, 2wt% of xanthan gum, 4wt% of polyvinyl alcohol, 12wt% of inorganic filler, and the balance is water.
[0041] The defoaming aid is polyether modified silicone oil, and the preparation method of the polyether modified silicone oil is as follows: under nitrogen protection, 3 parts by weight of benzyl silicone oil, 3 parts by weight of (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide and 0.5 parts by weight of n-decanol and chloroplatinic acid are added and mixed, wherein the amount of chloroplatinic acid added is 0.02wt% of the mass of the benzyl silicone oil, the mixture is reacted at 90° C. and 400 rpm for 1.5 hours, 3 parts by weight of allyl polyoxyethylene methyl terminated polyether is added, and the reaction is continued for 5 hours, and the solvent is evaporated under reduced pressure to obtain the polyether modified silicone oil.
[0042] The inorganic filler is modified nano silicon dioxide; the preparation method of the modified nano silicon dioxide comprises the following steps:
[0043] N1: 6 parts by weight of nano-silica are dispersed in 30 parts by weight of water, 2 parts by weight of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane are added, the pH is adjusted to 4.5, and the mixture is reacted at 80° C. and 400 rpm for 2 h, then cooled to room temperature, centrifuged, washed, and freeze-dried to obtain silane-modified nano-silica;
[0044] N2 Under nitrogen protection, 5 parts by weight of the above-mentioned silane-modified nano-silica was dispersed in 60 parts by weight of water, stirred at room temperature and 600 rpm for 10 min, 3.5 parts by weight of N-vinyl-N-methylacetamide and 0.05 parts by weight of ammonium persulfate were added, and stirring was continued for 10 min. The mixture was reacted at 600 rpm and 80°C for 6 h, and then washed and dried to obtain modified silica.
[0045] The preparation method of the defoamer for cementing cement comprises the following steps:
[0046] S1 weigh the above raw materials according to weight;
[0047] S2: Castor oil polyoxyethylene ether, polyether modified silicone oil, xanthan gum, polyvinyl alcohol, modified nano-silica and water are put into a reaction kettle, heated and stirred at 50° C. and 1000 rpm for 30 minutes to obtain a defoaming agent for cementing cement.
[0048] Example 2
[0049] A defoamer for cementing cement comprises the following raw materials in percentage by mass: 5wt% of castor oil polyoxyethylene ether, 7wt% of defoaming aid, 1wt% of xanthan gum, 6wt% of polyvinyl alcohol, 8wt% of inorganic filler, and the balance is water.
[0050] The defoaming aid is polyether modified silicone oil, and the preparation method of the polyether modified silicone oil is as follows: under nitrogen protection, 3 parts by weight of benzyl silicone oil, 3 parts by weight of (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide and 0.5 parts by weight of n-decanol and chloroplatinic acid are added and mixed, wherein the amount of chloroplatinic acid added is 0.02wt% of the mass of the benzyl silicone oil, the mixture is reacted at 90° C. and 400 rpm for 1.5 hours, 3 parts by weight of allyl polyoxyethylene methyl terminated polyether is added, and the reaction is continued for 5 hours, and the solvent is evaporated under reduced pressure to obtain the polyether modified silicone oil.
[0051] The inorganic filler is modified nano silicon dioxide; the preparation method of the modified nano silicon dioxide comprises the following steps:
[0052] N1: 6 parts by weight of nano-silica are dispersed in 30 parts by weight of water, 2 parts by weight of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane are added, the pH is adjusted to 4.5, and the mixture is reacted at 80° C. and 400 rpm for 2 h, then cooled to room temperature, centrifuged, washed, and freeze-dried to obtain silane-modified nano-silica;
[0053] N2 Under nitrogen protection, 5 parts by weight of the above-mentioned silane-modified nano-silica was dispersed in 60 parts by weight of water, stirred at room temperature and 600 rpm for 10 min, 3.5 parts by weight of N-vinyl-N-methylacetamide and 0.05 parts by weight of ammonium persulfate were added, and stirring was continued for 10 min. The mixture was reacted at 600 rpm and 80°C for 6 h, and then washed and dried to obtain modified silica.
[0054] The preparation method of the defoamer for cementing cement comprises the following steps:
[0055] S1 weigh the above raw materials according to weight;
[0056] S2: Castor oil polyoxyethylene ether, polyether modified silicone oil, xanthan gum, polyvinyl alcohol, modified nano-silica and water are put into a reaction kettle, heated and stirred at 50° C. and 1000 rpm for 30 minutes to obtain a defoaming agent for cementing cement.
[0057] Example 3
[0058] A defoamer for cementing cement comprises the following raw materials in percentage by weight: 10 wt% of castor oil polyoxyethylene ether, 4 wt% of defoaming aid, 3 wt% of xanthan gum, 2 wt% of polyvinyl alcohol, 20 wt% of inorganic filler, and the balance is water.
[0059] The defoaming aid is polyether modified silicone oil, and the preparation method of the polyether modified silicone oil is as follows: under nitrogen protection, 3 parts by weight of benzyl silicone oil, 3 parts by weight of (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide and 0.5 parts by weight of n-decanol and chloroplatinic acid are added and mixed, wherein the amount of chloroplatinic acid added is 0.02wt% of the mass of the benzyl silicone oil, the mixture is reacted at 90° C. and 400 rpm for 1.5 hours, 3 parts by weight of allyl polyoxyethylene methyl terminated polyether is added, and the reaction is continued for 5 hours, and the solvent is evaporated under reduced pressure to obtain the polyether modified silicone oil.
[0060] The inorganic filler is modified nano silicon dioxide; the preparation method of the modified nano silicon dioxide comprises the following steps:
[0061] N1: 6 parts by weight of nano-silica are dispersed in 30 parts by weight of water, 2 parts by weight of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane are added, the pH is adjusted to 4.5, and the mixture is reacted at 80° C. and 400 rpm for 2 h, then cooled to room temperature, centrifuged, washed, and freeze-dried to obtain silane-modified nano-silica;
[0062] N2 Under nitrogen protection, 5 parts by weight of the above-mentioned silane-modified nano-silica was dispersed in 60 parts by weight of water, stirred at room temperature and 600 rpm for 10 min, 3.5 parts by weight of N-vinyl-N-methylacetamide and 0.05 parts by weight of ammonium persulfate were added, and stirring was continued for 10 min. The mixture was reacted at 600 rpm and 80°C for 6 h, and then washed and dried to obtain modified silica.
[0063] The preparation method of the defoamer for cementing cement comprises the following steps:
[0064] S1 weigh the above raw materials according to weight;
[0065] S2: Castor oil polyoxyethylene ether, polyether modified silicone oil, xanthan gum, polyvinyl alcohol, modified nano-silica and water are put into a reaction kettle, heated and stirred at 50° C. and 1000 rpm for 30 minutes to obtain a defoaming agent for cementing cement.
[0066] Comparative Example 1
[0067] A defoamer for cementing wells comprises the following raw materials in percentage by weight: 8wt% of castor oil polyoxyethylene ether, 17wt% of a defoaming aid, 2wt% of xanthan gum, 4wt% of polyvinyl alcohol, and the balance being water.
[0068] The defoaming aid is polyether modified silicone oil, and the preparation method of the polyether modified silicone oil is as follows: under nitrogen protection, 3 parts by weight of benzyl silicone oil, 3 parts by weight of (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide and 0.5 parts by weight of n-decanol and chloroplatinic acid are added and mixed, wherein the amount of chloroplatinic acid added is 0.02wt% of the mass of the benzyl silicone oil, the mixture is reacted at 90° C. and 400 rpm for 1.5 hours, 3 parts by weight of allyl polyoxyethylene methyl terminated polyether is added, and the reaction is continued for 5 hours, and the solvent is evaporated under reduced pressure to obtain the polyether modified silicone oil.
[0069] The preparation method of the defoamer for cementing cement comprises the following steps:
[0070] S1 weigh the above raw materials according to weight;
[0071] S2: Castor oil polyoxyethylene ether, polyether modified silicone oil, xanthan gum, polyvinyl alcohol and water are put into a reaction kettle, heated and stirred at 50° C. and 1000 rpm for 30 minutes to obtain a defoaming agent for cementing cement.
[0072] Comparative Example 2
[0073] A defoamer for cementing cement comprises the following raw materials in percentage by weight: 8wt% of castor oil polyoxyethylene ether, 2wt% of xanthan gum, 4wt% of polyvinyl alcohol, 17wt% of inorganic filler, and the balance is water.
[0074] The inorganic filler is modified nano silicon dioxide; the preparation method of the modified nano silicon dioxide comprises the following steps:
[0075] N1: 6 parts by weight of nano-silica are dispersed in 30 parts by weight of water, 2 parts by weight of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane are added, the pH is adjusted to 4.5, and the mixture is reacted at 80° C. and 400 rpm for 2 h, then cooled to room temperature, centrifuged, washed, and freeze-dried to obtain silane-modified nano-silica;
[0076] N2 Under nitrogen protection, 5 parts by weight of the above-mentioned silane-modified nano-silica was dispersed in 60 parts by weight of water, stirred at room temperature and 600 rpm for 10 min, 3.5 parts by weight of N-vinyl-N-methylacetamide and 0.05 parts by weight of ammonium persulfate were added, and stirring was continued for 10 min. The mixture was reacted at 600 rpm and 80°C for 6 h, and then washed and dried to obtain modified silica.
[0077] The preparation method of the defoamer for cementing cement comprises the following steps:
[0078] S1 weigh the above raw materials according to weight;
[0079] S2: Castor oil polyoxyethylene ether, xanthan gum, polyvinyl alcohol, modified nano-silica and water are put into a reaction kettle, heated and stirred at 50° C. and 1000 rpm for 30 minutes to obtain a defoaming agent for cementing cement.
[0080] Comparative Example 3
[0081] A defoamer for cementing cement comprises the following raw materials in percentage by mass: 8wt% of castor oil polyoxyethylene ether, 5wt% of defoaming aid, 2wt% of xanthan gum, 4wt% of polyvinyl alcohol, 12wt% of inorganic filler, and the balance is water.
[0082] The defoaming aid is polyether modified silicone oil, and the preparation method of the polyether modified silicone oil is as follows: under nitrogen protection, 3 parts by weight of benzyl silicone oil, 3 parts by weight of (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide and 0.5 parts by weight of n-decanol and chloroplatinic acid are added and mixed, wherein the amount of chloroplatinic acid added is 0.02wt% of the mass of the benzyl silicone oil, the mixture is reacted at 90° C. and 400 rpm for 1.5 hours, 3 parts by weight of allyl polyoxyethylene methyl terminated polyether is added, and the reaction is continued for 5 hours, and the solvent is evaporated under reduced pressure to obtain the polyether modified silicone oil.
[0083] The inorganic filler is nano silicon dioxide.
[0084] The preparation method of the defoamer for cementing cement comprises the following steps:
[0085] S1 weigh the above raw materials according to weight;
[0086] S2: Castor oil polyoxyethylene ether, polyether modified silicone oil, xanthan gum, polyvinyl alcohol, nano silicon dioxide and water are put into a reaction kettle, heated and stirred at 50° C. and 1000 rpm for 30 minutes to obtain a defoaming agent for cementing cement.
[0087] Comparative Example 4
[0088] A defoamer for cementing cement comprises the following raw materials in percentage by mass: 8wt% of castor oil polyoxyethylene ether, 5wt% of defoaming aid, 2wt% of xanthan gum, 4wt% of polyvinyl alcohol, 12wt% of inorganic filler, and the balance is water.
[0089] The defoaming aid is polyether modified silicone oil, and the preparation method of the polyether modified silicone oil is as follows: under nitrogen protection, 3 parts by weight of benzyl silicone oil, 3 parts by weight of (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide and 0.5 parts by weight of n-decanol and chloroplatinic acid are added and mixed, wherein the amount of chloroplatinic acid added is 0.02wt% of the mass of the benzyl silicone oil, the mixture is reacted at 90° C. and 400 rpm for 1.5 hours, 3 parts by weight of allyl polyoxyethylene methyl terminated polyether is added, and the reaction is continued for 5 hours, and the solvent is evaporated under reduced pressure to obtain the polyether modified silicone oil.
[0090] The inorganic filler is modified nano-silica; the preparation method of the modified nano-silica comprises the following steps: dispersing 6 parts by weight of nano-silica in 30 parts by weight of water, adding 2 parts by weight of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, adjusting the pH to 4.5, reacting at 80° C. and 400 rpm for 2 hours, cooling to room temperature, centrifuging, washing, and freeze-drying to obtain silane-modified nano-silica.
[0091] The preparation method of the defoamer for cementing cement comprises the following steps:
[0092] S1 weigh the above raw materials according to weight;
[0093] S2: Castor oil polyoxyethylene ether, polyether modified silicone oil, xanthan gum, polyvinyl alcohol, modified nano-silica and water are put into a reaction kettle, heated and stirred at 50° C. and 1000 rpm for 30 minutes to obtain a defoaming agent for cementing cement.
[0094] Comparative Example 5
[0095] A defoamer for cementing cement comprises the following raw materials in percentage by mass: 8wt% of castor oil polyoxyethylene ether, 5wt% of defoaming aid, 2wt% of xanthan gum, 4wt% of polyvinyl alcohol, 12wt% of inorganic filler, and the balance is water.
[0096] The defoaming aid is benzyl silicone oil.
[0097] The inorganic filler is modified nano silicon dioxide; the preparation method of the modified nano silicon dioxide comprises the following steps:
[0098] N1: 6 parts by weight of nano-silica are dispersed in 30 parts by weight of water, 2 parts by weight of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane are added, the pH is adjusted to 4.5, and the mixture is reacted at 80° C. and 400 rpm for 2 h, then cooled to room temperature, centrifuged, washed, and freeze-dried to obtain silane-modified nano-silica;
[0099] N2 Under nitrogen protection, 5 parts by weight of the above-mentioned silane-modified nano-silica was dispersed in 60 parts by weight of water, stirred at room temperature and 600 rpm for 10 min, 3.5 parts by weight of N-vinyl-N-methylacetamide and 0.05 parts by weight of ammonium persulfate were added, and stirring was continued for 10 min. The mixture was reacted at 600 rpm and 80°C for 6 h, and then washed and dried to obtain modified silica.
[0100] The preparation method of the defoamer for cementing cement comprises the following steps:
[0101] S1 weigh the above raw materials according to weight;
[0102] S2: Castor oil polyoxyethylene ether, benzyl silicone oil, xanthan gum, polyvinyl alcohol, modified nano-silica and water are put into a reaction kettle, heated and stirred at 50° C. and 1000 rpm for 30 minutes to obtain a defoaming agent for cementing cement.
[0103] Test Example 1
[0104] Defoaming test experiment: Weigh 10g of oil-based flushing agent and put it into a constant speed stirrer, add 120g of water, stir at 5000rpm for 20s, after stirring, pour the solution and foam in the stirring cup of the constant speed stirrer into the measuring cylinder, measure and record the solution volume V1 including the foam volume. Take 0.3g of the defoaming agent for cementing cement of Examples 1-3 and Comparative Examples 1-5 and slowly add it to the above solution volume V1 along the edge of the inner wall of the measuring cylinder. Start timing after adding, and the solution volume V5 at 1min. Defoaming rate = (V1-V5) / (V1-325)×100%, test 5 times for each group, take the average value, and the results are shown in Table 1.
[0105] Table 1 Defoaming performance test results
[0106]
[0107] Test Example 2
[0108] Basic performance test: Tested with reference to JGJ / T70-2009 "Standard for Basic Performance Test Methods of Building Mortar", the defoamers for cementing cement prepared in Examples 1-3 and Comparative Examples 1-5 were respectively formulated into cement mortar: 50 parts by weight of cement, 16 parts by weight of fly ash, 100 parts by weight of sand, 10 parts by weight of kaolin, 10 parts by weight of epoxy resin emulsion, 30 parts by weight of water, 1 part by weight of sodium polyacrylate, 1.5 parts by weight of the defoamer prepared in Examples 1-5, and 2 parts by weight of sodium lignin sulfonate. The prepared cement mortar was transported to the laboratory 24 hours in advance, placed at 20°C, stirred for 5 minutes using a mortar mixer, and made into a prismatic test mold with a size of 40mm×40mm×160mm, and a cavity with a diameter of 6.5mm was opened at each of the two end faces of the test mold. Three groups of parallel samples were tested, and the average value was taken. The results are shown in Table 2.
[0109] Table 2 Basic performance test results
[0110]
[0111] It can be seen from Tables 1 and 2 above that the defoaming agent for cementing cement prepared by the present invention has good defoaming performance, and has good anti-shrinkage performance and anti-penetration performance when used in cement mortar, and can effectively avoid cracking, hollowing and falling off, which not only reduces the weight of the building, but also reduces the construction cost of the construction project.
[0112] Examples 1-3 show better effects than Comparative Examples 1-5, mainly due to the optimization of the raw materials and preparation methods used. In the examples, the synergistic effect of polyether-modified silicone oil and modified silicon dioxide is fully exerted, and the dispersibility and stability of the defoamer in cement are improved through precise proportioning and specific preparation process. This not only improves the defoaming efficiency, but also enhances the mechanical properties and anti-permeability of the cement slurry.
[0113] Comparing Example 1 and Comparative Examples 1-2, it can be seen that in the present invention, the characteristics of modified nano-silica and polyether-modified silicone oil and their interaction provide significant synergistic synergy for cement mortar. Modified nano-silica is prepared by polymerization reaction of silane-modified nano-silica and N-vinyl-N-methylacetamide under the action of an initiator. The material has excellent surface properties and high dispersibility, effectively preventing the formation and aggregation of bubbles in cement, improving the compactness and uniformity of cement, thereby enhancing the anti-seepage and anti-shrinkage properties of cement. On the other hand, the preparation of polyether-modified silicone oil involves the heating reaction of benzyl silicone oil, (2S)-3-(adjacent allyloxyphenoxy)-1,2-propylene oxide and n-decanol under chloroplatinic acid catalysis, and the introduced allyl polyoxyethylene methyl-terminated polyether enhances its hydrophilicity and reactivity, making it easy to disperse in cement mortar, effectively reducing surface tension, rapidly destroying bubbles, and improving defoaming efficiency. Polyether-modified silicone oil and modified nano-silica not only show their own independent characteristics in cement mortar, but also further enhance the overall performance of cement through interaction. Due to its excellent interfacial activity and hydrophilicity, polyether-modified silicone oil can quickly diffuse to the bubble interface in cement mortar, reduce surface tension, accelerate the rupture of bubbles, and reduce the impact of bubbles on the integrity of cement structure. At the same time, its modified molecular structure remains stable under highly alkaline cement mortar conditions, ensuring a long-lasting defoaming effect. Modified nano-silica, through its unique surface modification and nano-scale size, not only enhances its dispersibility and compatibility in the cement matrix, but also fills in the microscopic pores of cement mortar, reduces porosity, improves the fluidity and plasticity of cement paste, and helps to improve the mechanical strength and durability of cement. The synergistic effect of these properties significantly improves the long-term stability and crack resistance of cement structure, providing a cost-effective solution for the preparation of high-performance cement mortar.
[0114] Comparing Comparative Examples 3 and 5, polyether-modified silicone oil is added as a defoaming aid in Comparative Example 3, which can solve the problem of weak defoaming property and low foam suppression ability of the defoaming agent. As a defoaming aid, polyether-modified silicone oil can effectively reduce the formation of bubbles in cement slurry. It hinders the formation and aggregation of bubbles by reducing the surface tension of cement slurry, thereby reducing the number and size of bubbles in cement slurry. The emulsifying function of the emulsifier can disperse the polyether-modified silicone oil into fine particles, which is conducive to the spreading of polyether on the foam surface, better inhibiting the formation of foam or breaking the foam, thereby improving the defoaming property of the defoaming agent.
[0115] Comparing Comparative Examples 3-4, the addition of modified silica in Comparative Example 4 can effectively hinder the formation and aggregation of bubbles. Its special surface properties and structure can form a microstructure similar to a mesh structure in the cement slurry, hindering the diffusion and aggregation of bubbles in the cement slurry, thereby effectively reducing the number and size of bubbles and improving the defoaming effect. As an inorganic filler, modified silica has excellent mechanical properties and stability, and can effectively interact with cement particles to form a uniform and stable cement slurry structure. This structure helps to improve the fluidity and pumpability of the cement slurry, making it easier to flow and fill in the wellbore, thereby improving the rheological properties of the cement slurry, and can effectively increase the shrinkage resistance and impermeability of the cement slurry.
Claims
1. A defoamer for cementing, characterized in that: Including the following raw materials: emulsifier, defoaming agent, thickener, dispersant, modified nano-silica, water; The preparation method of the modified nano silicon dioxide comprises the following steps: N1: 6-8 parts by weight of nano-silica are dispersed in 25-60 parts by weight of water, 1-3 parts by weight of N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane are added, the pH is adjusted to 4-5, and the mixture is reacted at 70-90° C. and 300-500 rpm for 1-4 hours, then cooled to room temperature, centrifuged, washed, and freeze-dried to obtain silane-modified nano-silica; N2 Under nitrogen protection, 3-7 parts by weight of the above silane-modified nano-silica is dispersed in 50-100 parts by weight of water, stirred at room temperature and 500-800 rpm for 8-15 minutes, 3-5 parts by weight of N-vinyl-N-methylacetamide and 0.03-0.1 parts by weight of ammonium persulfate are added, stirring is continued for 5-12 minutes, and the mixture is reacted at 400-800 rpm and 70-90° C. for 4-10 hours, washed, and dried to obtain modified silica; The defoaming aid is polyether modified silicone oil, and the preparation method of the polyether modified silicone oil is as follows: under nitrogen protection, 2-5 parts by weight of benzyl silicone oil, 2-5 parts by weight of (2S)-3-(o-allyloxyphenoxy)-1,2-propylene oxide and 0.2-0.7 parts by weight of n-decanol and chloroplatinic acid are added and mixed, wherein the amount of chloroplatinic acid added is 0.005-0.02wt% of the mass of the benzyl silicone oil, the reaction is carried out at 80-100°C and 300-600rpm for 1-4h, and then 2-5 parts by weight of allyl polyoxyethylene methyl terminated polyether are added to continue the reaction for 3-8h, and the solvent is evaporated under reduced pressure to obtain the polyether modified silicone oil.
2. The defoamer for cementing according to claim 1, characterized in that: The invention comprises the following raw materials in percentage by weight: 5-10 wt% of emulsifier, 4-7 wt% of defoaming aid, 1-3 wt% of thickener, 2-6 wt% of dispersant, 8-20 wt% of inorganic filler and the balance is water.
3. The defoamer for cementing according to claim 1, characterized in that: The emulsifier is at least one of castor oil polyoxyethylene ether, polyethylene glycol dilaurate, sorbitan polyoxyethylene ether fatty acid ester, and Tween 80.
4. The defoamer for cementing according to claim 1, characterized in that: The thickener is at least one of xanthan gum, sodium alginate, sodium starch phosphate and sodium alginate.
5. The defoamer for cementing according to claim 1, characterized in that: The dispersant is at least one of polyethylene glycol, polyvinyl alcohol, polyethyleneimine and tributyl phosphate.
6. The method for preparing a defoamer for cementing according to any one of claims 1 to 5, characterized in that: The steps include: S1 weigh the above raw materials according to weight; S2: putting emulsifier, defoaming agent, thickener, dispersant, inorganic filler and water into a reaction kettle, heating and stirring to obtain a defoaming agent for cementing cement.
Citation Information
Patent Citations
A defoaming branched condensate, a defoaming agent composition and its preparation method
CN115594838B
Polyether modified silicone oil defoaming agent for coating, and preparation method thereof
CN113368542A
Defoaming agent for oil well cement and preparation method thereof
CN117902851A